The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3171/2018.2.spine171003
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive posterior cervical foraminotomy with tubes to prevent undesired fusion: a long-term follow-up study

Abstract: OBJECTIVEThe objective of this study was to compare anterior cervical discectomy and fusion (ACDF) and minimally invasive posterior cervical foraminotomy (MI-PCF) with tubes for the treatment of cervical radiculopathy in terms of the 1) overall revision proportion, 2) index and adjacent level revision rates, and 3) functional outcome scores.METHODSThe authors retrospectively reviewed the records of consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Instability issues after partial facetectomy during PF may lead problems that require fusion, in general fusion after PF have rates of up to 5%. Recent retrospective studies of minimal invasive PF with over 1000 cases shown that a good level of decompression is achieved, i.e., to same or better NDI in comparison to ACDF [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
See 1 more Smart Citation
“…Instability issues after partial facetectomy during PF may lead problems that require fusion, in general fusion after PF have rates of up to 5%. Recent retrospective studies of minimal invasive PF with over 1000 cases shown that a good level of decompression is achieved, i.e., to same or better NDI in comparison to ACDF [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…The preserved motion may lead to restenosis as the degeneration continues with the risk of secondary surgery on the index level [34]. PF will lead to clinical success in 64-96% with a reoperation incidence of 4-7% in retrospective cohort studies [22][23][24][25][26][27][28][29][30][31][32][35][36][37].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Based on a solid body of evidence, MI-PCF is a successful alternative surgery to reduce problems such as false joints, adjacent segment diseases, and anterior-related complications. MI-PCF does not necessitate the patient giving up a cervical spine motion segment, and it has a lower complication rate, a lower cost, and a faster return to movement ( 50 , 51 ). Based on the findings of this study, PCF, similar to other interventions, produced satisfactory results, with no statistical difference in postoperative success rates, post-operative complication rates, or postoperative working status, which is consistent with previous study findings ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall six studies were included in quantitative synthesis including four studies that directly compare MIS-PCF to ACDF, one study that directly compares MIS-PCF to TDA, and one study that compares MIS-PCF to both ACDF and TDA. [53][54][55][56][57][58] A flow chart of study inclusion and exclusion is shown in Figure 1.…”
Section: Systematic Reviewmentioning
confidence: 99%